Pedagogical Explorations in a Posthuman Age : Essays on Designer Capitalism, Eco-Aestheticism, and Visual and Popular Culture as West-East Meet /: Essays on Designer Capitalism, Eco-Aestheticism, and Visual and Popular Culture as West-East Meet. (2020) - jagodzinski, jan
No abstract available